Case report of a 66-year-old woman with atypical takotsubo syndrome and concomitant coronary artery disease. Issue 2 (13th February 2020) - Niederseer, David; Ghadri, Jelena Rima; Manka, Robert; Templin, Christian
Abstract : Takotsubo syndrome is increasingly recognised worldwide. As both, takotsubo syndrome and acute myocardial infarction can present with similar findings, including chest pain, elevated troponin and creatine kinase, it is often difficult to differentiate these conditions. Here, we present a challenging case that illustrates (1) difficulties to diagnose takotsubo syndrome in the presence of a significant coronary artery stenosis; (2) how takotsubo syndrome could be misdiagnosed as acute coronary syndrome if diagnostic workup does not include echocardiography or left ventriculography; (3) the importance of cardiac MRI which can contribute to the diagnosis of takotsubo syndrome.